Finitude and death in Western society: a reflection focusing on health professionals - Raylane da Silva Machado; Larissa Alves de Araújo Lima; Grazielle Roberta Freitas da Silva; Claudete Ferreira de Souza Monteiro; Silvana Santiago Rocha (Universidad de Alicante, 2016)
Aim: to carry out a reflection on how the vision of finitude/death in Western society influences the performance of health professionals. Method: A reflection on death and dying is performed using the main classical authors working this issue. Results: Death and dying are events not only biological but also of religious, social, philosophical and anthropological dimension. In Western society, there is a trend away from the idea of death, with a false belief of immortality. It is difficult to think about the issue of death and dying in their process aspects and its multiple meanings. This view implies that death is unwarranted or unexpected. Conclusions: When we reflect directly on the practices of health professionals towards death, we understand that an opening for discussion of the topic among their peers and also is necessary to society in general. That's because these workers have turned academic training to rehabilitate and restore health with a view to prolonging life, thus envisage death as a failure, professional failure, which leads to feelings of guilt and sadness. It is important, therefore, that these professionals are trained scientifically and psychologically to deal with the issue.